Permeability of the Retina and RPE-Choroid-Sclera to Three Ophthalmic Drugs and the Associated Factors - Hyeong Min Kim; Hyounkoo Han; Hye Kyoung Hong; Ji Hyun Park; Kyu Hyung Park; Hyuncheol Kim; Se Joon Woo (MDPI AG, 2021)
In this study, Retina-RPE-Choroid-Sclera (RCS) and RPE-Choroid-Sclera (CS) were prepared by scraping them off neural retina, and using the Ussing chamber we measured the average time-concentration values in the acceptor chamber across five isolated rabbit tissues for each drug molecule. We determined the outward direction permeability of the RCS and CS and calculated the neural retina permeability. The permeability coefficients of RCS and CS were as follows: ganciclovir, 13.78 ± 5.82 and 23.22 ± 9.74; brimonidine, 15.34 ± 7.64 and 31.56 ± 12.46; bevacizumab, 0.0136 ± 0.0059 and 0.0612 ± 0.0264 (×10−6 cm/s). The calculated permeability coefficients of the neural retina were as follows: ganciclovir, 33.89 ± 12.64; brimonidine, 29.83 ± 11.58; bevacizumab, 0.0205 ± 0.0074 (×10−6 cm/s). Between brimonidine and ganciclovir, lipophilic brimonidine presented better RCS and CS permeability, whereas ganciclovir showed better calculated neural retinal permeability. The large molecular weight drug bevacizumab demonstrated a much lower permeability than brimonidine and ganciclovir. In conclusion, the ophthalmic drug permeability of RCS and CS is affected by the molecular weight and lipophilicity, and influences the intravitreal half-life.